СОСТОЯНИЕ РАЗВИТИЯ БРЕНДИНГА В РЕСПУБЛИКЕ КАЗАХСТАН - Ережепова, Ж А (Journal of Economic Research & Business Administration, 2015)
In article the basic branding characteristics, as one of major factors of increase of competitiveness of the goods are considered. Specific features and parameters of brands are analyzed, recommendations on their creation are given.